النموذج البنائي للنزعة للمحاجة وتقديم الذات والسلوك القيادي لدى ذوي الأدوار الإشرافية في التعليم - الميلبي، بندر بن صلاح عتيق (جامعة عين شمس - مركز الإرشاد النفسي, 2017)
dis study aimed to come up with a structural model that reflects teh relationship among teh variables of teh study. Teh study sample consisted of (602) educational leader in teh Department of Education of teh Province of Yanbu. Teh researcher used teh following scales: Argumentativeness scale (Infante & Rancer, 1982), self-presentation scale (Bolino & Turnley, 1999), and multi-factors leadership scale (Avolio & Bass, 1995). Results of teh study concerning teh proposed structural model concluded that independent variable argumentativeness contribute statistically significant contribution in teh predictability of three types of leadership behavior as dependent variables. At teh same time, teh independent variable argumentativeness had statistically significant contribution, in an indirect and proportional way, in teh prediction of teh three types of leadership behavior as dependent variables, through teh dimensions of self-presentation as a mediating variables.
هدفت الدراسة الحالية التوصل إلى نموذج بنائي يجسد العلاقة بين متغيرات الدراسة. تكونت عينة الدراسة من (602) قائدا تربويا. استخدم الباحث: مقياس النزعة للمحاجة لـ "انفينت" و "رانسر" (Infante & Rancer, 1982)، مقياس تقديم الذات لـ "بولينو" و "تيرنلي" (Bolino & Turnley, 1999)، ومقياس القيادة متعددة العوامل لـ "باس" و "افوليو" (Avolio & Bass, 1999). خلصت نتائج الدراسة الخاصة باختبار النموذج البنائي المقترح إلى أن المتغير المستقل: النزعة للمحاجة يساهم مساهمة دالة إحصائيا، وعلى نحو مباشر ونسبي، في التنبؤ بالأنواع الثلاثة للسلوك القيادي: القيادة التحويلية، والقيادة التبادلية، والقيادة الترسلية، كمتغيرات تابعة؛ وفي ذات الوقت يساهم المتغير المستقل: النزعة للمحاجة مساهمة دالة إحصائيا، وبشكل غير مباشر ونسبي، في التنبؤ بالأنواع الثلاثة للسلوك القيادي: القيادة التحويلية، والقيادة التبادلية، والقيادة الترسلية، كمتغيرات تابعة، عبر أبعاد تقديم الذات كمتغيرات وسيطية وهي: أبعاد ترقية الذاتية، والحظوة، والمثالية، والتخويف، والتوسل.
Keywords: التعليم -- الإشراف التربوي -- القيادة التربوية -- النمذجة البنائية -- السلوك القيادي